Progressive concept evaluation method for automatically generated concept variants - Woldemichael, D.E. (EDP Sciences, 2014)
Conceptual design is one of the most critical and important phases of design process with least computer support system. Conceptual design support tool (CDST) is a conceptual design support system developed to automatically generate concepts for each subfunction in functional structure. The automated concept generation process results in large number of concept variants which require a thorough evaluation process to select the best design. To address this, a progressive concept evaluation technique consisting of absolute comparison, concept screening and weighted decision matrix using analytical hierarchy process (AHP) is proposed to eliminate infeasible concepts at each stage. The software implementation of the proposed method is demonstrated. Â© 2014 Owned by the authors, published by EDP Sciences.